Peran Kepemimpinan Kepala Desa dalam Meningkatkan Budaya Disiplin Kerja Bagi Aparatur Desa : Studi pada Pemerintahan Desa Sisobahili Siwalawa Kecamatan Hilisalawa'ahe Kabupaten Nias Selatan (Lembaga Pengembangan Kinerja Dosen, 2025)
Village government holds a strategic role in the delivery of public services, development, and local governance. However, the low level of work discipline culture among village apparatus and the role of village head leadership in improving it often become obstacles in optimizing government performance in serving the community. This research aims to describe the condition of work discipline among the apparatus, analyze the leadership role of the village head, identify obstacles, and formulate strategies to enhance the culture of discipline at the Government of Sisobahili Siwalawa Village, Hilisalawa’ahe District, South Nias Regency. This study employs a qualitative descriptive approach, using data collection techniques such as interviews, observation, and documentation. The results show that although some apparatus have demonstrated discipline, there remains inconsistency in attendance and responsibility. The village head has taken steps to build communication and enforce rules, but these efforts have not yet fully created a harmonious and disciplined work culture. The main obstacles include a lack of awareness of responsibilities, low work initiative, and inconsistent enforcement of sanctions. The strategies implemented include applying a participatory leadership style, fair delegation of tasks, and gradual enforcement of rules. This research provides important implications that the effectiveness of village head leadership significantly influences the formation of work discipline culture among village apparatus. A consistent, communicative, and exemplary approach is required to realize a professional village government.